Examining the Water Quality Situation in Klampok River, Semarang through the Application of the NSF-WQI (National Sanitation Foundation – Water Quality Index) Model - Syafrudin Syafrudin; Anik Sarminingsih; Henny Juliani; Anang Wahyu Sejati; Bimastyaji Surya Ramadan; Mochamad Arief Budihardjo; Winardi Dwi Nugraha (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
The Klampok River is one of the rivers that crosses the Bandungan, Bawen, Bergas and Pringapus Districts. The increase in the number of residents in the river basin which is not matched by the availability of land encourages the conversion of land functions that are not in accordance with their designation. The existence of the Klampok River as a water body receiving wastewater resulting from anthropogenic activities has caused the Klampok River to become polluted. Thus, it is important to study the water quality and water quality status of the Klampok River for nature conservation. This study aims to determine the water quality status of the Klampok River using the water quality index method, namely the National Sanitation Foundation – Water Quality Index (NSF-WQI) with reference to class II river water quality standards. NSF-WQI is a method that uses several specific parameters to determine river water quality.DO, fecal coliform, pH, BOD, nitrate, phosphate, temperature, turbidity, and total solids.The 2018 water quality index using the NSF-WQI method is in the range54.13 – 65.38with medium-good quality status. Meanwhile, the water quality index for 2019 using the NSF-WQI method is within the range35.47 – 66.60with moderate status, except for sampling point 6 which has bad status.